Decision Support System For Developing Application For Pharmaceutical Supplies Using The MMSL And Pareto Law Methods - Muchammad Aryo Puruhito; Achmad Zakki Falani (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2021)
This study discusses the design and manufacture of a decision support system for pharmaceutical supply needs using the MMSL and Pareto Law methods. The development of this decision support system aims to assist the planning process for pharmaceutical supply needs including: drugs and consumables, as well as to reduce the cost of pharmaceutical supplies. Problem analysis is done by observing and conducting feasibility studies of ongoing information systems, and analyzing problem findings. The data used for the main support of this decision support system is dummy data. The decision support system is made using the PHP and MySQL programming languages as the database and will be implemented based on a web base. The results of this study produce a web-based decision support system that can support the management of pharmaceutical supplies and provide accurate and effective reports.